ORGANIZATIONAL STRUCTURE OF THE INTERNAL CONTROL SERVICE FOR THE FULFILLMENT OF TAX OBLIGATIONS OF ENTERPRISES - Abdullayev, Abror; Djamalov , Hasan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Annotation. The article discusses the issues of the organizational structure of internal control over the fulfillment of tax obligations by business entities, internal and external factors taken into account in the process of creating its organizational structure, the functions and tasks of the internal corporate control service over the fulfillment of tax obligations of enterprises, and substantiates the feasibility of using tax management tools in the methodological support of this special type of accounting and analysis, tools have been developed to ensure the completeness, objectivity and reality of the results obtained, one of the effective methods of corporate tax management - internal control.